The rythm of aggression and the graveyard of solitude. Critical approach to the forms of discourse in Carlos Fuentes Where the Air is Clear (2015)
We try to study here the diverse forms of writing in the novel by Carlos Fuentes, Where the Air Is Clear (1958). The forms of writing are understood as modes of discourse in the way of building mental worlds, own mythology, conception of the sacred, myth, morals, the political and of the same literary creation. In this essay, we try to show how is structured a writing of domination, or the rhythm of aggression, here particularly a writing of the corrupt, in which structure is unmasked how the conception of ordinary, literary, political and historical speech and discourse, opens ways to a critique of language. © Instituto de Estética - Pontificia Universidad Católica de Chile.